Inhibitory activity of chitosan nanoparticles and Spirulina platensis extract against Candida albicans in thermally treated milk - Nazmy, Sara; Elbarbary, Hend A.; Mohamed, Hamdi A.; Awad, Dina A.B. (Journal of Advanced Veterinary Research, 2024)
Milk is a suitable medium for the growth of many microbes, in particular, fungi and yeasts that change the physical and chemical properties of milk and in the final dairy products. In the current study, the target was to apply natural components to control growth of Candida albicans in pasteurized milk. Chitosan (CS), chitosan nanoparticles (CSN), and Spirulina platensis (SP) and its extract (SPE) were used. The MIC (12.5 to 100 mg/ml) of the natural components against Candida albicans as a model for fungi family was determined their effect in broth and in pasteurized milk. CS and CSN were the most effective natural component inhibit the growth of C. albicans strain with concentration 25 mg/ml followed by SPE with inhibitory activity against C. albicans at concentration 100 mg/ml while, Spirulina platensis (SP) showed the least inhibitory activity with the same concentration. By application in pasteurized milk CSN showed the best candidacidal effect with inhibitory 1.2 log10cfu/ml after 15day at refrigerated storage as adding CSN extended shelf life of pasteurized milk. On conclusion, we recommend adding chitosan nanoparticles in milk at concentration 25mg/ml to limit the fungal growth